41st Conference of the International Council for Traditional Music: July 13–19, 2011, St. John’s, New Foundland, Canada - Jurková, Zuzana (Lidé města, 2011)
A World Conference of the International Council for Traditional Music (ICTM) takes place every two years, if possible each one on a different continent. This year’s in Canada (hosted by the Memorial University in St. John’s) was, in many respects, similar to the last one in the Republic of South Africa (2009) and the next-to-the-last one in Vienna (2007). Its themes were so broad that they provided the possibility of presentation of nearly every paper’s or panel’s topic; there were also film projections and complementary music workshops. The conference topics were: 1) Indigenous Modernities; 2) Cross-cultural Approaches to the Study of the Voice; 3) Rethinking Ethnomusicology through the Gaze of Movement; 4) Atlantic Roots/Routes; 5) Dialogical Knowledge Production and Representation: Implications and Ethics; 6) Acoustic Ecology; 7) New Research. More than three hundred active participants were involved in these themes, which made of the conference, rather than a place of concentration of the sharing of knowledge, some sort of a trade fair of data, theories, methodologies, methods…